Succinate is an inflammatory signal that induces IL-1β through HIF-1α - Tannahill, G. M.; Curtis, A. M.; Adamik, J.; Palsson-McDermott, E. M.; McGettrick, A. F.; Goel, G.; Frezza, C.; Bernard, N. J.; Kelly, B.; Foley, N. H.; Zheng, L.; Gardet, A.; et al. (Nature (London), 2013)
Succinate is identified as a metabolite in innate immune signalling, which leads to enhanced interleukin-1β production during inflammation. Succinate is an innate immunity signal The bacterial endotoxin lipopolysaccharide activates macrophages, as part of the innate immunity response, by inducing a shift from oxidative to glycolytic metabolism. Gillian Tannahill et al . show here that lipopolysaccharide increases levels of the tricarboxylic acid cycle intermediate succinate in macrophages through a metabolic process not previously reported in macrophages, the 'GABA shunt'. Succinate in turn drives the key pro-inflammatory cytokine interleukin-1β. Macrophages activated by the Gram-negative bacterial product lipopolysaccharide switch their core metabolism from oxidative phosphorylation to glycolysis 1 . Here we show that inhibition of glycolysis with 2-deoxyglucose suppresses lipopolysaccharide-induced interleukin-1β but not tumour-necrosis factor-α in mouse macrophages. A comprehensive metabolic map of lipopolysaccharide-activated macrophages shows upregulation of glycolytic and downregulation of mitochondrial genes, which correlates directly with the expression profiles of altered metabolites. Lipopolysaccharide strongly increases the levels of the tricarboxylic-acid cycle intermediate succinate. Glutamine-dependent anerplerosis is the principal source of succinate, although the ‘GABA (γ-aminobutyric acid) shunt’ pathway also has a role. Lipopolysaccharide-induced succinate stabilizes hypoxia-inducible factor-1α, an effect that is inhibited by 2-deoxyglucose, with interleukin-1β as an important target. Lipopolysaccharide also increases succinylation of several proteins. We therefore identify succinate as a metabolite in innate immune signalling, which enhances interleukin-1β production during inflammation.